(3Hjf GdfXQjI h GdJWHjbs - (3eMeO YHO GdaJGM(B, (3jGZjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2009)
(3WHjYI h CgejI GdJOQjH , GdJWhQ GdJGQjNj ddJOQjH , fXQjI GdfXe aj eLGd GdJOQjH GdGOGQj , JMOjO GdGMJjGLGJ GdJOQjHjI , GdJNWjW dJUeje GdHQGeL GdJOQjHjI , CfhGY GdJOQjH , JUeje GdHQGeL GdJOQjHjI , CSGdjH GdJOQjH GdGOGQj , Jbhje GdJOQjH , OhQ eYGgO GdGOGQI GdYGeI aj GdhWf GdYQHj aj GdJfejI GdGOGQjI h GdeTcdGJ GdJj JhGLggG (B.s
(3eQGLY (B: (3dcd aUd eQLY ; edGMb U(B.351 (3; agQS GdNQGFW h GdGTcGd (B: (3dcd Tcd UaMIs
Keywords: (3GdJNWjWs; (3GdJOQjHs; (3GdJOQjH GdGOGQjs; (3GdJfejI GdGOGQjIs